Peranan Guru dalam Meningkatkan Pemahaman Anak Sekolah Dasar materi Karakteristik Zat melalui Media Pembelajaran Audio Visual - Niken Nurrohmawati; Devi Zakiah Nur Khasanah; Wahyu Kurniawati (Publikasi Inspirasi Indonesia, 2023)
The role of the teacher is key in the learning process, which is the center of the entire educational process. Apart from their function as educators, teachers also have other important roles in carrying out the learning process. Teachers are educators who help students and their environment identify themselves as humans, role models and educators. In the learning process teachers can innovate learning by using learning media. Learning media is a tool to help teachers facilitate learning activities. Teachers can choose audio-visual learning media because with this media in learning teachers can directly explain and provide real evidence about the properties of substances in the hope that students can see, compare, understand, remember and prove what the teacher has conveyed to students. Apart from that, it can improve students' understanding by using audio-visual because this technology-based learning media will have a positive impact on students' ability and willingness to participate in learning activities. This research aims to determine the role of teachers in increasing elementary school children's understanding of the properties of materials and the properties of substances through audio-visual learning media. The research method used is a qualitative research method. The data collection technique used is library research. Teachers are educators, figures, role models and introducers to the students they teach and their environment